Designing and Developing Rechargeable Aluminium-Ion Battery using Graphite Coated Activated Charcoal Corncob as Cathode Material (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
One of the renewable energy storage systems that can be used today is the aluminum ion battery. In this study, aluminum foil was used as anode, polyetylene polyprophylene (PE/PP) as separator, electrolyte from AlCl3/[EMIm]Cl and graphite coated corncob, an activated charcoal, as cathode. Coating method of cathode materials was done by mixing both graphite and activated charcoal with varied composition 1:0.5, 1:1, 1:1.5, and 1:3. The coating process began by mixing the graphite and corncob with ethanol as a solvent for six hours, then heating in an oven at 80 °C for three days, gradual drying in a furnace at 350 °C for five hours and sintering at 600 °C for six hours. From this research, SEM results showed that carbon particles were evenly distributed, with spherical particles. The spherical shape was the main requirement of carbon formation in order to produce high energy. Based on the results, battery potential was 2.54 V with average of optimal capacity at a ratio of graphite and corncob activated charcoal 1:1.5 was 83.067 mAh/g. The highest efficiency was also at a ratio of 1:1.5 of 97.20%, because at this ratio, there was an increasing in percentage of element C 91.74%, greater than the percentage of element C on the other three cathode samples.Salah satu sistem penyimpan energi terbarukan yang bisa digunakan saat ini adalah baterai ion aluminium. Pada penelitian ini digunakan aluminium foil sebagai anoda, polyetylene polyprophylene (PE/PP) sebagai separator, elektrolit menggunakan AlCl3/[EMIm]Cl dan grafit terlapisi arang aktif tongkol jagung sebagai bahan katoda. Metode pelapisan bahan katoda dilakukan dengan mencampurkan grafit dan arang aktif dengan variasi komposisi 1:0,5, 1:1,1:1,5 dan 1:3. Proses pelapisan diawali dengan pencampuran grafit dan arang aktif tongkol jagung dengan ethanol sebagai pelarut selama enam jam kemudian pemanasan di oven pada suhu 80oC selama tiga hari, pengeringan bertahap di furnace pada suhu 350oC selama lima jam dan sintering pada suhu 600oC selama enam jam. Dari penelitian ini didapatkan hasil SEM menunjukkan bahwa partikel karbon terdistribusi merata, dengan bentuk partikel bulat (sphare).Sampelberbentuk bulat atau sphere merupakan syarat utama pembentukan karbon supaya dapat menghasilkan energi tinggi. Berdasarkan hasil uji baterai diperoleh potensial sebesar 2,54 Volt dengan rata-rata kapasitas optimal terjadi pada rasio grafit dan arang aktif tongkol jagung 1:1,5 sebesar 83,067 mAh/g. Efisiensi tertinggi juga terjadi pada rasio 1:1,5 sebesar 97,20%. Hal ini karena pada rasio 1:1,5 terjadi peningkatan persentase unsur C yakni 91.74% lebih besar dari persentase unsur C pada tiga sampel katoda yang lainnya.